Pemanfaatan Daun Kelor Sebagai Bahan Dasar Produk Olahan Makanan di Gampong Dayah Baroh - Lubis, Ahmad Singgih Ridwan; Zurba, Nabil; Edwarsyah, Edwarsyah; Marlian, Neneng; Fithria, Dewi (Universitas Teuku Umar, 2024)
The utilization of leaf moringa as a material-based product of processed food has had interesting attention for some years. Leaf moringa contains various substance important nutrients, including protein, fiber, vitamin A, vitamin C, substances iron, and calcium. properties nutrition This makes leaf moringa a material potential For developed become products valuable food _ nutrition high. Studies This aims to explore the potency utilization of leaf moringa in product processed food And give a description about profit the health it offers. dedication program public done on Mother Village PKK mother Dayah Baroh Subdistrict Ulim Regency Pidie Jaya. The method used _ in devotion This is method counseling with giving material related to introduction product moringa And mark nutrition, as well as providing training direct making tea leaf moringa And cake leaf moringa. Results from devotion to the public This is (1) knowledge participants about product-processed moringa And material raw making tea increased consecutive by 90%, (2) skills participants about the method of making processed moringa increased by 95%.